IS SOEGUAPRANATA CATHOLIC UNIVERSITY READY FOR INTERNATIONAL CLASSES? - Heny Hartono (Celt: A Journal of Culture, English Language Teaching & Literature, 2001)
Soegijapranata Catholic University which is one of the leading private universities in Semarang. Central Java, is plannring to run International Classes. The idea of establishing the International Classes should be supported by good preparation of all components involved in the teaching anli lea ing process. Running a class in English will create some new and perhaps unexpected problems. As the first step in preparing the International Classes. Soegijapranata Catholic University has held a teuher training for International Classes Preparation. The teacher training could be used as a reflection to answer the question: Is Soegijapranata Catholic University ready for the International Classes?